2015
DOI: 10.1002/cbm.1949
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of female mentally disordered offenders culpable under the new legislation in Japan: A gender comparison study

Abstract: There appears to be a particularly vulnerable sub-group of women with severe mood disorders, a history of serious suicide attempts and young children at risk of harming those children. Our sample was small and from a single unit so, given the potential importance of improving understanding of who is at risk in such circumstances, extending our study nationally seems indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 16 publications
10
15
0
Order By: Relevance
“…This also confirms a diagnosis profile of patients found under MTSA treatment from a single facility in our country (22); that is, female patients (28%) are more often diagnosed as F3 than male patients (4%). F3 diagnosis was also increasingly related to homicide in both present and previous studies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This also confirms a diagnosis profile of patients found under MTSA treatment from a single facility in our country (22); that is, female patients (28%) are more often diagnosed as F3 than male patients (4%). F3 diagnosis was also increasingly related to homicide in both present and previous studies.…”
Section: Discussionsupporting
confidence: 87%
“…The patient population was predominantly male (about 70%). Such male dominance in clinical offenders was consistently observed in previous Japanese studies, which comprised partially overlapping patients undergoing hospitalization for assessment (16) and under MTSA-based inpatient treatment (22, 23). Additionally, a study from the United States, recruiting patients under involuntary inpatient treatment who committed serious violence, reported that male patients tended to more often commit violent acts several months before treatment admission than female patients (24).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The perpetrator produced alibi evidence to investigators following the murder, showing a high level of planning irrespective of the psychotic ideation. The majority of murder offenses were committed by males, a well-replicated finding across different countries and continents (Häkkänen-Nyholm et al, 2009;Kristoffersen et al, 2014;Matejkowski et al, 2008;Nagata et al, 2016), who, in general, were younger than female offenders at the date of the index offense. Female and male co-offenders were younger than solitary offenders, hinting at group interactions being more important in younger age or growing independency with ongoing aging.…”
Section: Discussionmentioning
confidence: 76%
“…Besides the psychiatric diagnosis, it is important to point out that women usually express antisocial behavior in ways that are different from that of men (46,47). In most homicides committed by women, the victim is a family member (5,18,48,49), especially a child (where the diagnosis of the perpetrator is typically a schizophrenic disorder) (42,50,51) or their partner (34), rather than strangers who are killed more frequently by men (39,51). The psychopathic dimension seems to play a major role in those infrequent homicides committed by women who kill victims outside of their family (18).…”
mentioning
confidence: 99%